Analisis Risiko pada Usahatani Padi dengan Sistem Irigasi Pompa di Desa Pattinoang - Nur Asmirani; Sri Mardiyati; Nadir Nadir (Department of Agribusiness, Halu Oleo University, 2022)
Rice is the principal food commodity that the Indonesian people rely on to meet their fundamental requirements. This study aims to determine the level of production and income of rice farming with an irrigation system in Pattinoang Village and determine the level of production risk, price risk, and income risk in rice farming using a pump irrigation system in Pattinoang Village. This study took place between February to April of 2022. The information gathered in this study is based on original data from 32 farmers. Coefficient of Variation (CV) and income analysis was used to examine the data. The result revealed that rice farmers in Pattinoang Village were producing at a high level, with an average production of 4.219 kg/ha/Planting Season and average revenue of IDR5.919.364,28/ha/Planting Season, with a total production cost of IDR10.136.528,80/ha/Planting Season and total revenue of IDR16.055.893,07/ha/Planting Season. Based on the Coefficient of Variation (CV) analysis, the coefficient of variation in production risk is 0,016. The coefficient of variation in price risk is 0,001, and the coefficient of variation in income risk is 0,020, so the levels of production risk, price risk, and income risk of rice farmers in Pattinoang Village are classified as low risk.